(untitled) (Web of Teachers: Inderscience Research, 2024)
This article analyzes financial literacy programs in Finland and examines ways to adapt them to the conditions of Uzbekistan. Emphasizing that financial literacy has a positive impact on economic stability and well-being of the population, the study notes the need for cooperation between the public and private sectors, the organization of special courses and training in educational institutions, as well as the use of modern technology. Suggestions and recommendations developed on the basis of the Finnish experience are of great importance in the formation of practical programs aimed at improving financial literacy in the school system of Uzbekistan.